(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
Since the return to democracy in our country, many different movements, having different aims appeared. Among them, those which would strug- gle for the defence of women’s rights. The province of La Pampa has not been exempt from this fenomenon. In a period of more than three decades flourished in the pampean social scenery several movements. Nontheless, it is about the end of the 20th century that many other emerged, whose objectives are clearly feminist, and they are bound to the express defence of women’s rights. This is the case of Movement for Women’s Rights of General Pico”, subject of study in this paper. Adopting a regional perspective, from a gender viewpoint, this research is powered by the following question- ings: Did the constitution of this movement implied a resignification and reconstruction of both, individual and collective identities of its mem- bers? In what sense? In which context do they decide to group? Which were, a still are their aims? Which lines of action do they have? Have they achieved any goals? Which ones?